Evaluación de la prevalencia de parásitos gastrointestinales en ovinos mediante tres técnicas coproparasitarias en la parroquia San Pablo de Atenas cantón San Miguel provincia de Bolívar - Villacres Gòmez, Jaime Geovanny (2022)
"Evaluation of the prevalence of gastrointestinal parasites in sheep through three coproparasitic techniques in the parish of San Pablo de Atenas, San Miguel canton, province of Bolivar", whose objectives are: to determine the most common gastrointestinal parasites that affect the health of sheep, establish the degree of infestation through coproparasitic techniques in sheep and identify which of the techniques has greater efficiency in the determination of gastrointestinal parasites. The methodology used for this work was descriptive statistics, the delimitation of the study site was found, followed by the establishment of the variables to be studied, in order to choose the sample analysis techniques which were: direct feces, sedimentation and flotation, finally the methodology for the tabulation of data was chosen, which was by means of the Excel program. As a result of the research, the most common gastrointestinal parasites in sheep were Strongylus with 34.8%, Eimeria with 14.1%, Ostetargia with 13.6% and Chabertia with 13.2%. In addition, it was found that the degree of infestation can be related to factors such as sex, age and weight of the sheep, with the highest number of parasites observed in male animals aged 0-2 years with 34.8%, a range of 20-40 Kg. This is due to the fact that the amount of parasites is related to weight, since these cause a low weight due to loss of appetite; it was also identified that the most effective techniques were direct feces with 28% and flotation with 58% being the most effective, between the two samples show a similarity in the results.